Connective tissue nevus with peripheral linear ramifications. - Milano, A. (European Journal of Pediatric Dermatology, 2011)
A 10-year-old child was observed due to the presence of a lesion of the right thorax and arm diagnosed as scleroderma. The mother reported that the lesion had been present for several years, but could not specify how many. Since she had noticed the lesion, it had not changed. The child felt a sensation of tingling when sweating and applying ointment. Physical examination showed a plaque with indistinct boundaries of the right arm and clavicle. In the latter site the plaque continued to healthy skin with radiated projections (Fig. 2). Keratosis pilaris was more pronounced on the plaque than on the contralateral arm and there was slight erythema. At palpation the skin was thickened and hardened. The histological examination (Fig. 3) showed only a thickened dermis, and the staining of elastic fibers did not show significant alterations. The final diagnosis was connective tissue nevus.